Incidencia del método High Intensity Interval Training en la condición física de los estudiantes universitarios. - Peña, Patricia Moraima (2019)
The application of the training method of high intensity intervals in the physical condition is studied. The approach presented by the research was of a quantitative type of longitudinal type because it was carried out at two specific moments of time, twice with each individual (pre-post), reaching a quasi-experimental level, and of a correlational type. The study design was a randomized controlled trial with a control group and an experimental group. The HIIT intervention was an 8-week work intervention supervised by the author of this work. Students were asked to participate in three HIIT sessions per week, the same durations that lasted 8 minutes for the first 2 weeks, 10 minutes for weeks 3, 4 and 5 and for the last 12 minutes for 6.7 and 8 weeks, duration and a relationship 30 seconds rest work. Evaluations were performed by taking the Course Navette test, which measures cardiorespiratory fitness. The study population consisted of 150 university-level students, 91 female subjects and 54 male subjects with an average age of 20.48 years ± 2.05. Through the investigation it was possible to diagnose the physical condition of university students, which has a maximum oxygen consumption of 36.25 ml / kg / min, with a standard deviation of ± 6.62, and can be classified as a poor physical condition. By verifying the hypothesis using the Wilcoxon signed range test, which is a non-parametric test to compare the average range of two related samples, it was possible to establish the influence of the high intensity interval interval method on the physical condition of the University students. With a P value of 0 and less than 0.05, the null hypothesis can be rejected with 95.0% confidence.